DIGITAL LEADERSHIP, ORGANIZATIONAL LEARNING, AND EDUCATIONAL INNOVATION: A MULTILEVEL ANALYSIS OF UNIVERSITY PERFORMANCE IN THE DIGITAL ERA - Mohamad Shabri Hatlah; Muh. Arif; Harti Tanaiyo; Ibnu Rawandhy N. Hula (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
The development of digital technology is driving significant transformation in higher education management, particularly in aspects of leadership, organizational learning, and educational innovation. This study aims to analyze the influence of digital leadership and organizational learning on educational innovation and its implications on university performance through a multilevel approach. The study used a quantitative approach with an explanatory design, involving 178 respondents consisting of lecturers and education staff at Ichsan Gorontalo Utara University. Data was collected through a Likert scale questionnaire and analyzed using SEM-PLS with the help of SmartPLS 4.0 and supported by multilevel analysis. The results showed that digital leadership had a significant effect on organizational learning (β = 0.66; t = 8.12; p < 0.001), organizational learning had a significant effect on educational innovation (β = 0.59; t = 7.45; p < 0.001), and educational innovation had a significant effect on university performance (β = 0.63; t = 8.01; p < 0.001). In addition, educational innovation was shown to partially mediate the relationship between digital leadership and institutional performance (β = 0.40; t = 6.32; p < 0.001). The results of the multilevel analysis showed an ICC value of 0.19–0.23 which indicates a significant influence between organizational levels. This study concludes that digital transformation in higher education requires the integration of digital leadership, organizational learning, and educational innovation in a systemic manner to improve institutional performance.